Sternal Anomalies in Asymptomatic Patients after Median Sternotomy and Potential Influencing Factors - Rodriguez Cetina Biefer, Hector; Sündermann, Simon H.; Alkadhi, Hatem; Genoni, Michele; Maisano, Francesco; Emmert, Maximilian Y.; Plass, André (The Thoracic and Cardiovascular Surgeon, 2018)
Background We aimed to assess asymptomatic patients who had open-heart surgery with median sternotomy for potential sternal anomalies (SA), their related patient-specific risk factors, and treatment options for the prevention of SA.Methods Multiplanar CT scans (CTs) from 131 asymptomatic consecutive patients were analyzed retrospectively. Of these, 83 underwent CABG (63.4%), and 48 had aortic valve (AV) procedures via median sternotomy. Sternal bone healing was analyzed for SA and their exact location.Results In total, 49 SA were identified in 42 (32.1%) patients; 65% SA were found in the manubrium (n = 32). Five hundred thirty-two wires were implanted (4.2 ± 0.5 wires/patient), out of which 96.1% (n = 511) were figure 8 wires. There was no difference between normal and abnormal sterna with regard to the number of wires used for sternal closure (4.2 ± 0.5 vs. 4.3 ± 0.6, p = ns). The distance between wire placement to the proximal edge of the manubrium in normal and abnormal sterna was comparable (11.2 ± 4.2 vs. 10.9 ± 4.8 mm, p = ns). Patients who underwent CABG had a significantly higher risk for SA (OR = 2.4, p ≤ 0.05, 95% CI [1.2–4.9]). The use of BIMA (OR = 4.4, p ≤ 0.05, 95% CI [1.1–17.9]) and body mass index (BMI) > 31 kg/m2 (OR = 3.4, p ≤ 0.01, 95% CI [1.4–8.3]) significantly increased the risk of SA.Conclusion At least 30% of patients were at an increased risk for SA after receiving a median sternotomy. CABG, use of BIMA, and a BMI > 30 kg/m2 were potential risk factors for the development of SA and warrant close clinical follow-up. Sternal plate fixation, particularly in the manubrium, could be beneficial in such patients.
Keywords: surgery; complications; sternum; outcomes; wound; healing